Stephen A. Douglas, Western Man: The Early Years in Congress, 1844-1850. - Ankrom, Reg. ([Place of publication not identified] : McFarland and Company, Inc. : McFarland, 2021)
"It didn't take long for freshman Congressman Stephen A. Douglas to see the truth of Senator Thomas Hart Benton's warning: slavery attached itself to every measure that came before the U.S. Congress. Douglas wanted to expand the nation into an ocean-bound republic. Yet slavery and the violent conflicts it stirred always interfered, as it did in 1844 with his first bill to organize Nebraska. In 1848, when America acquired 550,000 square miles after the Mexican War, the fight began over whether the territory would be free or slave. Henry Clay, a slave owner who favored gradual emancipation, packaged territorial bills from Douglas's committee with four others. But Clay's "Omnibus Bill" failed. Exhausted, he left the Senate, leaving Douglas in control. Within two weeks, Douglas won passage of all eight bills, and President Millard Fillmore signed the Compromise of 1850. It was Douglas's greatest legislative achievement. This book chronicles how his popular sovereignty doctrine moved the issue of slavery from Congress to the ballot box"--
Prologue -- Part One -- 1. "I am a Western man" -- 2. Douglas Runs for Congress -- 3. U.S. Representative Stephen A. Douglas of Illinois -- 4. "This chrysalis state, between worm and butterfly" -- 5. "Steam engine in breeches" -- 6. Public Works -- 7. Manifest Destiny -- 8. When Is Enough Enough? -- 9. Re-Election and Re-Annexation -- 10. Simplify, Simplify -- 11. Douglas and "Squatter Sovereignty" -- 12. Climate, Soil, Productions -- Part Two -- 13. The American Claim on Oregon -- 14. Why Oregon? -- 15. "Enthusiasms of pearly youth" -- 16. Friends and Foes -- 17. "Notice will be given" -- 18. Douglas Does His Homework -- 19. "A lion in the way" -- 20. "The whole of Oregon is ours" -- 21. Elevating the Level of Statesmanship -- 22. The Surprising Pre-Emption of Wilmot -- 23. Senator Stephen A. Douglas -- 24. Rumors of War -- 25. Polk -- 26. Douglas Seeks a Military Commission -- 27. Wilmot Creates a Southwestern Earthquake 28. Wilmot and a Challenge to Lead 29. Free Soil. Free Labor. For Free White Men 30. Advancement 31. Oregon--Free or Slave? 32. Weighing Wilmot and the Missouri Compromise 33. The Long Lament of John C. Calhoun -- 34. Douglas, the West, and Rails -- 35. Encountering Slavery 36. Southern Fears -- 37. Having It Both Ways -- Part Three -- 38. A Principle for Compromise -- 39. Death of a President -- 40. Golden California -- 41. Missouri -- 42. "Young America" -- 43. "California, do it yourself" -- 44. Henry Clay Going and Coming -- 45. Triumvirates Major and Minor -- 46. "A higher law" -- 47. "Fraud elected a president and senator" -- 48. Douglas Warns the South -- 49. Compromising Without Compromising -- 50. Groundwork for Compromise -- 51. Clay -- 52. The Omnibus's Wheels Come Off -- 53. The Rise of the Douglas Bills -- 54. Fugitives and Trade -- 55. Taking It to the House -- 56. Villain or Victor? -- Epilogue -- Appendix A: Resolution of the Chicago Common Council Adopted October 21, 1850 -- Appendix B: Douglas Resolutions at Chicago Meeting, Adopted October 23, 1850 -- Chapter Notes -- Bibliography -- Index.
Vendor-supplied metadata.
eBooks on EBSCOhost
Keywords: Douglas, Stephen A. -- 1813-1861.; Douglas, Stephen A. -- 1813-1861 -- Political and social views; United States. -- Congress. -- House -- Biography; United States. -- Congress. -- Senate -- Biography; Democratic Party (U.S.) -- History -- 19th century; États-Unis. -- Congress. -- Senate -- Biographies; Douglas, Stephen A. -- 1813-1861; Democratic Party (U.S.); United States. -- Congress. -- House; United States. -- Congress. -- Senate; Legislators -- United States -- Biography; Democracy -- United States -- History -- 19th century; Legislators -- Illinois -- Biography; United States -- Politics and government -- 1815-1861.; Parlementaires -- États-Unis -- Biographies; États-Unis -- Politique et gouvernement -- 1815-1861.; HISTORY / United States / 19th Century; POLITICAL SCIENCE / American Government / Legislative Branch; Democracy; Legislators; Political and social views; Politics and government; Illinois; United States; 1800-1899; Biographies; History